Fault in our stars - Boone, Josh, 1979-; Weber, Michael H. (Screenwriter); Neustadter, Scott; Godfrey, Wyck; Bowen, Marty; Woodley, Shailene; Elgort, Ansel, 1994-; Dern, Laura; Trammell, Sam, 1971-; Wolff, Nat, 1994-; Dafoe, Willem; Green, John, 1977-; et al. (Los Angeles, California West Hollywood, California Fox 2000 Pictures Temple Hill Productions, 2014)
Hazel and Gus share a sarcastic sense of humor, a distaste for the conventional, and ultimately a love that sweeps them on an unforgettable journey. Although the two teens face unlikely challenges with their health, their courage and dedication to each other prove that while life isn't perfect, love can still be extraordinary in this powerfully moving film based on John Green's New York Times best-selling novel.
Based on the novel by John Green.
Originally released as a motion picture in 2014.
Bonus features: Promotional featurettes: The Cast, The Making of The Fault in Our Stars, The Transformation, Literature to Life, Our Little Infinity, The Music Behind Our Stars; Gallery; Audio commentary by director Josh Boone & author John Green; Theatrical trailer.
Director of photography, Ben Richardson ; costume desinger, Mary Clare Hannan ; music, Mike Mogis & Nathaniel Walcott ; film editor, Robb Sullivan ; production designer, Molly Hughes.
Shailene Woodley, Ansel Elgort, Laura Dern, Sam Trammell, Nat Wolff, Willem Dafoe.
MPAA Rating: PG-13; for thematic elements, some sexuality and brief strong language ; Canadian Home Video Rating: PG.
Keywords: Green, John, -- 1977- -- Film and video adaptations; Teenagers -- Drama; Cancer -- Patients -- Drama; Self-help groups -- Drama; Love -- Drama; Man-woman relationships -- Drama; Interpersonal relations -- Drama; Terminally ill -- Drama; Love -- Drama; Adolescents; DVD-Video discs; Feature films -- Young adult; Romance films -- Young adult; Film adaptations -- Young adult; Video recordings for the hearing impaired -- Young adult; Video recordings for people with visual disabilities -- Young adult; Drama